Pengendalian Internal Terhadap Persediaan Cpo Pada Pt. Perkebunan Nusantara IV Regional 1 - Silitonga, Jesica KD; Sinurat, Mangasa; Siboro, Danri Toni (Jurnal Ekonomika Dan Bisnis (JEBS), 2025)
This study was conducted at PT Perkebunan Nusantara IV Regional 1, aimed at understanding and analyzing theimplementation of internal control over Crude Palm Oil (CPO) inventories at PT Perkebunan Nusantara IV Regional 1. Theresearch employed a descriptive qualitative approach with data collected through interviews and documentation studies.The results indicate that the internal control system in the company is functioning quite well and contributes positively tooperational smoothness. Physical control systems are conducted routinely and integrated to minimize losses, damages, andquality degradation during storage. However, there is a need to improve the frequency and quality of physical supervision as well as to enforce stricter procedures to detect and prevent deviations more proactively. Overall, the internal controls implemented have a positive influence on the efficiency and effectiveness of CPO inventory management in the company.